Amji kin cukrêj jakràjti kôt, me pancaca xà impejti pê Memõrtumre-Kanela jõ amji kin kôt haren xá/ Os valores culturais Memõrtumre-Kanela por meio de objetos sagrados e enfeites rituais - Canela, Oziel Irongukre (2021)
This study presents the amji kin cukrêj of my Memõrtumre-Kanela people that were used in the past or are still used today in rituals, seeking to value and strengthen the culture of my people and to stimulate the contact of the youngest people with this knowledge. For this, I chose some ritual objects for research and documented their stories through interviews and participant observation. I also searched for information about Canela ritual objects in museums, thinking about the importance of Canela pieces in the world of nonindigenous people. These pieces are the cultural heritage of my people. Within our culture, sacred objects represent our stories, identity, the right and the value of being indigenous people.